1999
DOI: 10.1139/cjfas-56-3-347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interannual variation in growth and condition on haddock recruitment

Abstract: Abstract:The relationship between recruitment and spawner biomass assumes that estimates of spawner biomass are proportional to total egg production by the stock. The validity of this assumption is in question for long-lived gadoid stocks; however, estimating total egg production independently of spawner biomass is seldom feasible. An alternative approach is to examine correlations between recruitment and variables likely to be proxies for total egg production by the stock. This indirect approach was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…Raldúa et al (2007) reported more prevalence of liver pathologies in fish at sites with higher wholebody mercury concentrations. Our results support that the morphometric measurement of fish condition is a simple cost-effective measure of its well being, particularly because condition generally affects growth, reproduction and survival (Adams 1999;Marshall and Frank 1999). Although the fecundities observed in our study were within the ranges of other studies for the same species (Crivelli 1981;Vila-Gispert and Moreno-Amich 2000), we detected significantly low values at the impacted area for carp and pumpkinseed.…”
Section: Comparison Of Life History Traitssupporting
confidence: 83%
“…Raldúa et al (2007) reported more prevalence of liver pathologies in fish at sites with higher wholebody mercury concentrations. Our results support that the morphometric measurement of fish condition is a simple cost-effective measure of its well being, particularly because condition generally affects growth, reproduction and survival (Adams 1999;Marshall and Frank 1999). Although the fecundities observed in our study were within the ranges of other studies for the same species (Crivelli 1981;Vila-Gispert and Moreno-Amich 2000), we detected significantly low values at the impacted area for carp and pumpkinseed.…”
Section: Comparison Of Life History Traitssupporting
confidence: 83%
“…As such, condition is a crucial parameter for the success of fish populations, since it may influence individual survival (Lambert and Dutil 2000), migration patterns (Slotte 1999), reproductive output (Blanchard et al 2003;Trippel and Neil 2004) and recruitment (Marshall and Frank 1999). Condition may be dependent on several, often interconnected, factors such as density dependence (Winters and Wheeler 1994), hydro-climatic conditions (Lloret and Rätz 2000), parasitic infection (Bagamian et al 2004) and selective fishing (Vainikka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…r Positive associations between condition and recruitment have been observed for both demersal (Marshall & Frank 1999) and pelagic (Boyd et al 1998) stocks. r For Georges Bank haddock the fit of the S/R relationship was improved if estimates of spawning stock biomass excluded the first-time spawners (Wigley 1999 r For Northeast Arctic cod the total lipid energy in the livers of mature females showed a positive, linear correlation with recruitment over a 50-year time period (Marshall et al 2000).…”
Section: Proxies For Maternal Effects On Recruitmentmentioning
confidence: 98%